A plea for extension of the official nomenclature of the microscopic structure of human tissues and organs, the Terminologia Histologica - Varga, I; Kachlík, D; Klein, M (Folia morphologica, 2020)
BACKGROUND: At first sight, the issue of terminology in morphological sciences may seem as "closed and changeless chapter", as many of the structures within the human body have been known for centuries. However, the exact opposite is true. Terminologia Histologica: International Terms for Human Cytology and Histology published under the Federative International Programme on Anatomical Terminology in 2008 is a new standard in human cell and tissue terminology. The list of items in the first and still valid official nomenclature of cellular and tissue structures, the Terminologia Histologica (TH), is the best and most extensive of all the histological nomenclatures ever issued. MATERIALS AND METHODS: The aim of this article is a systematic and in-depth analysis of the current internationally accepted nomenclature TH, with focus on important histological structures which are missing in this first edition. Some should be incorporated just for the sake of completeness and consistence, others are purely absent terms for individual structures or some are recently described new tissue structures. RESULTS: We also discuss about a question, how to deal with the issue of eponyms. Eponyms reflect medicine's rich and colourful history. Although they have not been considered official terms in the anatomical nomenclature since 1955, they are still widely used in clinical practice. CONCLUSIONS: We hope that this opinion article will develop a wide scientific discussion before the publication of the second edition, so perhaps the mentioned minor flaws will be corrected, so the new edition of the TH will become truly an internationally accepted communication tool for all histologists, histopathologists and anatomists.
Keywords: terminologie jako téma; Basement Membrane; Terminology as Topic; histology; Organ Specificity; terminology; Terminologia Histologica; nomenclature; Humans; histopathology; lidé; orgánová specificita; Proto-Oncogene Proteins c-kit; protoonkogenní proteiny c-kit; bazální membrána